The Effort of Immigrant for Survival in a New Country, Study Case: Russia - Juniar Laraswanda Umagapi (Jurnal Ilmiah Hubungan Internasional, 2018)
In this essay presents a critical understanding about immigrant way of living in a new country. Russia as a country with the big geographical aspect that also become a house for immigrant have their own special way to handle the immigrant. How the immigrant can socialize with the new environment and the issue facing for them as the newcomer in one society, how they get a proper job and how the culture difference influences their daily life will get analysed in this paper.  This research is conducted in Russia and use a qualitative research method such as interviewing, data analysis, graph, table, book, journal, article, newspaper and news to answer the research question. This research will give the contribution how the issue of immigrant influences the life of native people, how they contribute to the society and how the Russian government policy dealt with the negative stereotype about immigrant in Russia then how we would help immigrants thrive, these are the question that this research will help to answer. Keywords: Immigrant, Russia, culture difference, thrive, Russian government